Representation of Mental Health Issues in the Movie Not Okay - Nasya Fairuzya Ramadhani; Yudha Wirawanda (Jurnal ISO: Jurnal Ilmu Sosial, Politik dan Humaniora, 2024)
In this study, researchers will discuss the issue of scenes that represent how mental health issues are presented in the film Not Okay. The method in this research is a descriptive study using a qualitative approach. The population of this research is all the characters from the film Not Okay. Danni Sanders, the main character in the film Not Okay, is the subject or sample of the research. Data is collected through cutscene analysis which represents mental health issues through conversations and scenes which will be divided into several categories. Apart from verbal communication, researchers will also analyze non-verbal cues such as facial expressions because they can also be used to convey implied messages. The result of this research is the film "Not Okay" (2022), which succeeded in providing an in-depth and realistic depiction of the complexity of mental health issues. The main characters can encourage viewers to consider the need to recognize and understand mental health issues, as well as how external circumstances and support networks play an important role in the recovery process. As a result, the film is not only entertaining but also makes a significant contribution to increasing awareness and understanding of people facing mental health problems.